PENGARUH LEVERAGE, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Jimmy Winata; Lukman Surjadi (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to determine the effect of leverage, dividend policy, and firm size on firm value in manufacturing companies listed on the Indonesian stock exchange during 2018-2020. The sample was selected using purposive sampling method and 39 companies valid data. The data processing technique uses multiple regression analysis assisted by the Eviews 12 SV Lite program and Microsoft Excel 2010. The results of this study indicate that leverage and dividend policy do not have a significant effect on firm value while firm size has a significant effect on firm value. Leverage has no effect on firm value because companies tend to fund their assets with their own capital. Dividend policy has no significant effect on firm value because most investors do not see how much dividends distributed by the company to shareholders. Firm size has a negative and significant effect on firm value, which means the bigger the company, the lower the value of the company.